A study on perception and behavior among chinese urban and rural older adults in the early stage of COVID-19 - Yu, Lei; Zhuang, Xi (Association for Scientific Computing Electrical and Engineering (ASCEE), 2022)
Based on the comparison of information behavior characteristics and differences of the urban and rural elderly group in the early stage of the COVID-19 pandemic, this study aims to analyzed the questionnaires collected from 980 elderly people. It was found that there were different mechanisms by which media use influenced the protective behaviors of the elderly. Authoritative media is able to directly influence the behavior of the elderly, the information function of social media influences their precautionary measures by affecting their perception, and their social function directly promotes the adoption of protective behaviors by the elderly. There are still significant differences in media use between urban and rural elderly groups. Rural elderly groups rely more on interpersonal networks to seek information and their social circles of WeChat acquaintance are closer. Therefore, health communication research among the elderly needs to further focus on the urban-rural differences in their digital inclusion process.